Concentração plasmática de diclofenaco sódico em cães, submetidos à fonoforese - Pelizzari, C.; Raiser, A. G.; Mazzanti, A.; Souza, S. F.; Martins, V. M. V.; Peccinini, Rosangela Goncalves [UNESP]; Campos, M. L. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2012)
The aim of this study was to evaluate the plasma concentration of diclofenac sodium (DS) in dogs submitted to diclofenaco phonophoresis and to evaluate if phonophoresis induces greater absorption of this drug in dogs. Five dogs were used in eight different groups at different times: One group received oral administration of 40mg of DS per dog and seven groups received topical application of emulgel DS. The topical application area was 20cm(2). A continuous ultrasound frequency of 1MHz and intensity of 0.4W cm(-2) was used. Blood collections were performed before the treatment (T0), and 1h (T1) and 4h (T2) after ultrasound application for all groups. DS concentrations in plasma were measured by high performance liquid choramatohraphy (HPLC). There was significant increase of DS plasma concentration only at T1 in the oral administration group. It was not possible to detect any concentration of DS in the plasma of dogs after topical application of DS, even after DS phonophoresis. The facilitation of transdermal penetration by ultrasound has not been verified under the protocol specified in this research.
Plasma concentration of diclofenac sodium in dogs submitted to diclofenac phonophoresis
Keywords: dog; sonophoresis; diclofenac sodium; HPLC